Marketing Strategy Improvement to Acquire Walk-In-Guest and Increasing Online Presence of an Airport Lounge - Hartono, Anggia Fadhilah; Hidayati, Aprihatiningrum (Politeknik Pariwisata NHI Bandung, 2023)
Purpose of the study: This paper aims to understand various internal and external environmental marketing factors of Concordia Lounge Denpasar International in order to develop a marketing strategy that can increase the number of walk-in guest customers. Design/methodology: The research conducted is descriptive qualitative research which aims to describe and understand a phenomenon or situation in depth. The research was conducted using primary and secondary data obtained through document analysis, interviews, and observation. Findings: There are two gaps in the company's expectations and perceptions of the Concordia Lounge brand image, namely the perception of consumers who consider Concordia Lounge as an all-you-can-eat dining place compared to a waiting room and consumer perceptions stating that Concordia Lounge is no different from other lounges. Moreover, this study also found nine key success factors for marketing the Airport Lounge Research limitations/Implications: The limitation of this research is the design of a marketing strategy for Concordia Lounge Denpasar International and its B2C segmentation (walk-in guest). This research has the role of analyzing internal and external conditions that occur, and then a marketing strategy plan will be formulated with a focus on segmenting, targeting, positioning, and marketing mix. Novelty/Originality of the study: This research was conducted to develop an effective marketing strategy for Concordia Lounge Denpasar International that can help the management to determine and develop strategic steps in solving problems that exist in the company and can assist the company in improving its performance in the future.